Teachers' gestures for building listening and spoken language skills. Issue 10 (26th November 2022) - Montiegel, Kristella
ABSTRACT: This study investigates teachers' gestures produced during directive actions. I examine three particular gestures—pointing to the mouth, pointing to the ear, and cupping the ear— that teachers frequently deployed when interacting with their deaf or hard-of-hearing students in an oral preschool classroom, a setting focused on spoken language and listening. Using conversation analysis, I find that teachers' gestures occurred in sequences involving multiple directives to students and were routinely produced as subsequent directives, following students' noncompliance or displays of trouble related to teachers' initial directives. These gestural directives are used in two main instructional contexts: when targeting students' linguistic abilities and when managing classroom conduct. The findings reveal a paradox whereby teachers' gestures contribute to the classroom goal of socialization into oral communication, despite them being nonverbal resources in a setting that overtly prioritizes spoken language. Data consists of 25 hours of video recordings in one oral classroom in California.